The Effect of Administering Vitamin C Lozenges Towards the Increasing of Saliva Secretion of Hemodialysis Patient - Afeus Halawa; Fajar Amanah Ariga; Robin Ferdiansyah Sitopu; Devi Ardila; Fera Maria; Sari Siregar, Patimah (Caring: Indonesian Journal of Nursing Science, 2022)
Hemodialysis is a dialysis method to secrete bodily fluid when the kidneys are progressively or acutely unable to do it. This research aims to know the effect of administering vitamin C lozenges on the increasing saliva secretion of hemodialysis patients. The research used an experimental design with one group pre-test and post-test design. The T-test result was mostly dependent (paired sample test). A purposive sampling technique was used to acquire 30 hemodialysis patients. The result shows that 26 patients (86.7%) have an increase in saliva secretion while four patients (13.3%) have not. The p-value was 0.000 (p<0.05). It can be concluded that administering vitamin C lozenges to hemodialysis patients increases saliva secretion. This research suggests that Royal Prima Medan Public Hospital administer vitamin C lozenges as an alternative medicine to increase the saliva secretion of hemodialysis patients.